LITERASI KEUANGAN PADA GENERASI Z SEBUAH STUDI PADA MAHASISWA UNIVERSITAS MUHAMMADIYAH PALOPO - Putri lalimuga, Yosephine Injilitha; Goso, Goso; Halim, Ibrahim (Universitas Muhammadiyah Pontianak, 2025)
This study aims to measure the level of financial literacy, financial behavior and locus of control as independent variables, financial management as dependent variables and financial technology as moderating variables. The population in this study included students of Muhammadiyah University of Palopo in Palopo City. The sample of this study amounted to 240 students, selected using the census method where the researcher had determined the sampling by collecting data from the entire population that was the subject of the study. The data collection technique used a questionnaire. The results of this study indicate that financial literacy, financial behavior, and locus of control have a significant positive effect on financial management. The next result is that the financial technology variable also has a significant positive effect because it is able to moderate financial literacy, financial behavior, and locus of control on financial management. This study uses simple regression analysis and interaction tests or Moderated Regression Analysis (MRA), which are processed using the Statistical Package for Social Science (SPSS) version 26 program.